2021
DOI: 10.31273/reinvention.v14i1.722
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Sustainability into the Academic Institution

Abstract: This research examines environmental sustainability in the UK university context. Universities are prioritising sustainability commitments with many declaring a Climate Emergency, as well as recognising the importance of educating students about climate change. This research used a case-study approach in which semi-structured interviews were coupled with secondary data analysis, and suggests universities are pivotal for greater environmental sustainability. The results reiterate the urgent need to significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Unfortunately, the budget allocations make it impossible to compare Romania to other European countries in this regard [ 68 ]. The need to empower the young generation and make them the factors of change can be achieved through the teacher’s capacity [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the budget allocations make it impossible to compare Romania to other European countries in this regard [ 68 ]. The need to empower the young generation and make them the factors of change can be achieved through the teacher’s capacity [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although in previous research papers, the results revealed no interest in adding ESD competencies to the curriculum [ 69 ], now, through partnerships or by adding to their strategy in the University Charter for Sustainable Development, steps have been taken in this area [ 70 ]. The overcrowding of curricula, the apparent lack of significance to the curriculum, educational legitimacy, and limitations are cited as the key causes of institutions’ unwillingness to participate in sustainable education [ 62 ]. According to other researchers, for universities to become the drivers of sustainability issues and change agents, they must make sure that the needs of both the present and the future generations are better understood and built upon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the methodology used is qualitative, having as its main aims to assess (1) the adoption of ESD and also (2) the barriers encountered by universities in its implementation. The researchers opted for this type of approach as it offers deeper understanding regarding respondents’ opinions [ 28 ]. In addition, the authors decided in favor of a qualitative research because they considered that the analysis will be enriched with the examples provided by the participants, whereas the quantitative analysis did not provide this alternative.…”
Section: Methodsmentioning
confidence: 99%